Effect of apigenin and cisplatin on telomerase activity and expression of its structural proteins in triple negative breast cancer / Noorfaiza A.Aziz - A.Aziz, Noorfaiza (2016)
Almost 80 to 90% of cancer cells show a high telomerase activity compared to normal, differentiated cells. Telomerase activity in cancer cells depend on several factors: increased hTERT expression, modification of telomerase structural subunits and telomere associated proteins. In contrast to other breast cancer types, treatment options for Triple Negative Breast Cancer (TNBC) are limited due to a lack of specific molecular targets. Therefore, in this study the effect of apigenin, cisplatin and the combination of both on telomerase activity and structure was investigated in two different types of TNBC (MDA-MB-231 and HCC1806) and one control cell line (MCF10A). The transcriptional and translational expression of telomerase subunits namely Human telomerase reverse transcriptase (hTERT), Heat Shocked Protein 90 (Hsp90), Human Prostaglandin E synthase 3 (p23) as well as telomere-associated proteins; Telomeric Repeat Binding Factor-1 (TRF1), Telomeric Repeat Binding Factor-2 (TRF2), Protection of Telomere 1 (TIN2), TRF1 Interacting Protein 2 (POT1), POT1 and TIN2- Organizing Protein (TPP1) and Transcriptional Repressor/Activator Protein (RAP1) were measured using quantitative Real Time Polymerase Chain Reaction (qRT-PCR) and Enzyme-linked Immunosorbent Assay (ELISA). Apigenin with cisplatin showed synergistic effects with regards to increasing apoptosis and reducing telomerase activity in TNBC cells. However, the combined treatment did not show any protective effect on MCF10A cells. Reduction of telomerase activity by the combined treatment was associated with the reduction of Hsp90 and p23 expression in TNBC cells. The decrease of the shelterin subunits, POT1 and TPP1 after combined treatment also seem to be involved in regulating telomerase activity in TNBC cells. However, the deactivation of telomerase by the combination is strongly dependent on the subtype of TNBC used. In conclusion telomerase activity and shelterin components area potential target for the treatment of TNBC. However, further studies are required to investigate the effect of combined treatment in the non-tumour tissue. To date, this is the first study that demonstrated the synergistic effect of apigenin with cisplatin on TNBC cells.